2021
DOI: 10.1249/jsr.0000000000000854
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Thoracic Outlet Syndrome in Athletes — Nonsurgical Treatment Options

Abstract: Neurogenic thoracic outlet syndrome (NTOS) is an etiologically and clinically diverse disorder caused by compression of the brachial plexus traversing the thoracic outlet. Athletes who perform repetitive overhead activities are at risk of developing NTOS with sport-specific symptoms. This article reviews the controversial NTOS nomenclature, common sites of anatomic compression, and red flag symptoms that require immediate intervention. It also reviews the congenital, traumatic, and functional etiologies of NTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…A number of studies compare warfarin with oral anticoagulants at the lower-limb level [103], but a comparable analysis of fibrinolysis versus anticoagulation has not been evaluated in TOS. That said, beyond Paget-Schroetter Syndrome, although many authors still consider surgery the gold standard [104], despite the risks associated with surgery [105,106], nonsurgical treatment options (physical therapy, botulinum toxin injection, ultrasound-guided hydrodissection) have been proven to be effective in treating TOS [82,83,107] and are of interest in reducing the period following surgery during which sporting activities are discouraged.…”
Section: Influence Of Lifestyle On the Invasive Treatment Options For...mentioning
confidence: 99%
“…A number of studies compare warfarin with oral anticoagulants at the lower-limb level [103], but a comparable analysis of fibrinolysis versus anticoagulation has not been evaluated in TOS. That said, beyond Paget-Schroetter Syndrome, although many authors still consider surgery the gold standard [104], despite the risks associated with surgery [105,106], nonsurgical treatment options (physical therapy, botulinum toxin injection, ultrasound-guided hydrodissection) have been proven to be effective in treating TOS [82,83,107] and are of interest in reducing the period following surgery during which sporting activities are discouraged.…”
Section: Influence Of Lifestyle On the Invasive Treatment Options For...mentioning
confidence: 99%
“…Furthermore, conservative measures seem to be the best treatment option for patients with lower positions and hypermobility of the shoulder joint [93]. Warrick et al, in their study, found that surgical and non-surgical treatment had positive results in the treatment of nTOS in athletes who perform repetitive overhead movements [135]. Beteck et al compared the results of nTOS treatment between athletes and nonathletes.…”
Section: Risk Factors and Treatmentmentioning
confidence: 99%
“…Enquanto, se desconfiar de SDT nervosa é importante um bom exame neurológico clínico, com avaliação da função motora, sensorial e autonômica, com reconhecimento de sinais de fraqueza muscular (Dengler et al, 2022). Além disso, atletas que se exercitam de forma repetitiva e com uso de carga são mais propensos a adquirir a síndrome neurogênica (Warrick et al, 2021). A ressonância magnética é válida para identificação de causas relacionadas aos tecidos moles e a maioria dos pacientes com SDT são submetidos a vários exames de imagem para conclusão do diagnóstico (Huang et al, 2021).…”
Section: Compartimentounclassified